Scientific-Based Guided Inquiry Learning Model in Learning Chemistry in Class XI IPA Students of SMAN 1 Rote Timur - Cartika Candra Ledoh; Sentot Budi Raharjo; Sulistyo Saputro (Randwick International of Education and Linguistics Science Journal, 2021)
The purpose of this study is to determine the cognitive and effective learning outcomes of chemistry students using a scientifically based guided inquiry learning model. This study employed a quantitative methodology.. The population in this study consisted of 58 students from class XI at State Senior High School 1 Rote Timur, NTT For the 2019/2020 academic yea. Cluster random sampling was used to select the sample, which included two experimental and control classes. Tests, questionnaires, and observation sheets were used to collect data. The independent test samples t-test was used to analyze student learning outcomes. The finding showed that learning outcomes using the Scientific-Based Guided Inquiry Model and the direct method differs significantly from average high school learning outcomes. The results of the two aspects of learning outcomes, namely aspects of knowledge, and attitudes show a value of p <0.05 so that H0 is rejected and Ha is accepted. Thus, there are differences in student learning outcomes given the learning method using guided inquiry with students using conventional learning. However, from the results of data analysis, it was obtained that the p-value for the knowledge aspect was 0.000, the pvalue for the attitude aspect was 0.038.